2006
DOI: 10.1093/bioinformatics/btl423
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the insurgence of human genetic diseases associated to single point protein mutations with support vector machines and evolutionary information

Abstract: A beta version of the web tool is available at http://gpcr.biocomp.unibo.it/cgi/predictors/PhD-SNP/PhD-SNP.cgi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
573
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 778 publications
(598 citation statements)
references
References 24 publications
2
573
0
2
Order By: Relevance
“…homolog 1 (Mlh1), Structural maintenance of chromosomes protein 1B (Smc1b), and Testis-expressed gene 15 (Tex15) (Fig. 1B), were then evaluated with six additional tools that predict functional consequences of SNPs: Mutation Assessor, PANTHER, PhD-SNP, SNPs&GO, SNAP, and CADD (20)(21)(22)(23)(24)(25). Overall, each of these four nsSNPs was predicted to be deleterious by at least five of the eight computational algorithms used (Table 1).…”
Section: Significancementioning
confidence: 99%
“…homolog 1 (Mlh1), Structural maintenance of chromosomes protein 1B (Smc1b), and Testis-expressed gene 15 (Tex15) (Fig. 1B), were then evaluated with six additional tools that predict functional consequences of SNPs: Mutation Assessor, PANTHER, PhD-SNP, SNPs&GO, SNAP, and CADD (20)(21)(22)(23)(24)(25). Overall, each of these four nsSNPs was predicted to be deleterious by at least five of the eight computational algorithms used (Table 1).…”
Section: Significancementioning
confidence: 99%
“…Variant tolerance prediction methods included Mutation Taster [Schwarz et al, 2010], MutPred [Li et al, 2009], nsSNPAnalyzer [Bao et al, 2005], PhD-SNP [Capriotti et al, 2006], PMut [Ferrer-Costa et al, 2005], PolyPhen2 [Adzhubei et al, 2010], SIFT [Ng and Henikoff, 2003], SNAP [Bromberg and Rost, 2007], and SNPs&GO [Calabrese et al, 2009]. Sequence-based stability effect predictions were performed with SCPRED [Dosztányi et al, 1997], MUPRO [Cheng et al, 2006], and I-Mutant 3.0 [Capriotti et al, 2005], and structurebased predictions with SCide (stabilization centers) [Dosztanyi et al, 2003] and SRide (stabilizing residues) [Magyar et al, 2005] for MSH2 and MSH6 variants.…”
Section: Prediction Of Pathogenicitymentioning
confidence: 99%
“…The new method has an overall accuracy of 84% and area under the curve (AUC) of 0.91. When compared to a previously developed sequence-based method [Capriotti et al, 2006], an increase of 5% in the accuracy and AUC was observed.…”
Section: Prediction Of Variant Functionalitymentioning
confidence: 76%